HCV and flaviviruses hijack cellular mechanisms for nuclear STAT2 degradation: Up-regulation of PDLIM2 suppresses the innate immune response. - Michael A Joyce (PLoS Pathogens, 2019)
Host encounters with viruses lead to an innate immune response that must be rapid and broadly targeted but also tightly regulated to avoid the detrimental effects of unregulated interferon expression. Viral stimulation of host negative regulatory mechanisms is an alternate method of suppressing the host innate immune response. We examined three key mediators of the innate immune response: NF-KB, STAT1 and STAT2 during HCV infection in order to investigate the paradoxical induction of an innate immune response by HCV despite a multitude of mechanisms combating the host response. During infection, we find that all three are repressed only in HCV infected cells but not in uninfected bystander cells, both in vivo in chimeric mouse livers and in cultured Huh7.5 cells after IFNα treatment. We show here that HCV and Flaviviruses suppress the innate immune response by upregulation of PDLIM2, independent of the host interferon response. We show PDLIM2 is an E3 ubiquitin ligase that also acts to stimulate nuclear degradation of STAT2. Interferon dependent relocalization of STAT1/2 to the nucleus leads to PDLIM2 ubiquitination of STAT2 but not STAT1 and the proteasome-dependent degradation of STAT2, predominantly within the nucleus. CRISPR/Cas9 knockout of PDLIM2 results in increased levels of STAT2 following IFNα treatment, retention of STAT2 within the nucleus of HCV infected cells after IFNα stimulation, increased interferon response, and increased resistance to infection by several flaviviruses, indicating that PDLIM2 is a global regulator of the interferon response.